Simultaneous maxillary distraction osteogenesis using a Twin-Track distraction device combined with alveolar bone grafting in cleft patients: Preliminary report of a technique - Eduardo Yugo Suzuki (2018)
The simultaneous use of cleft reduction and maxillary advancement by distraction osteogenesis has not been applied routinely because of the difficulty in three-dimensional control and stabilization of the transported segments. This report describes a new approach of simultaneous bilateral alveolar cleft reduction and maxillary advancement by distraction osteogenesis combined with autogenous bone grafting. A custom-made Twin-Track device was used to allow bilateral alveolar cleft closure combined with simultaneous maxillary advancement, using distraction osteogenesis and a rigid external distraction system in a bilateral cleft lip and palate patient. After a maxillary Le Fort I osteotomy, autogenous iliac bone graft was placed in the cleft spaces before suturing. A latency period of six days was observed before activation. The rate of activation was one mm/d for the maxillary advancement and 0.5 mm/d for the segmental transport. Accordingly, the concave facial appearance was improved with acceptable occlusion, and complete bilateral cleft closure was attained. No adjustments were necessary to the vector of the transported segments during the activation and no complications were observed. The proposed Twin-Track device, based on the concept of track-guided bone transport, permitted three-dimensional control over the distraction processes allowing simultaneous cleft closure, maxillary distraction, and autogenous bone grafting. The combined simultaneous approach is extremely advantageous in correcting severe deformities, reducing the number of surgical interventions and, consequently, the total treatment time. © 2006 by The EH Angle Education and Research Foundation, Inc.